Blood pressure and body size preference in traditional communities of Ilorin metropolis, Nigeria. Issue 2 (June 2015) - Okoro, Emmanuel O.; Etebu, Ebitimitula N.; Oyejola, Benjamin A.
Abstract : Background: Our previous work showed that many individuals with type 2 diabetes and in the background population may prefer larger body sizes. This prompted us to study the interaction between body size, body size perception and blood pressure. Methods: Anthropometric variables, body size perception and blood pressure were measured in adults of three Nigerian communities. The results were subjected to tests of correlation and regression to determine any association/functional relationship between predictor variables and blood pressure. Results: Participants with elevated blood pressure were older (52.75 vs. 39.58 years) and had a higher BMI (24.50 vs. 22.84), waist circumference (86.69 vs. 81.57) and hip circumference (95.23 vs. 92.49) compared with normotensives. There were significant ( P <0.05) correlations between systolic blood pressure and age (0.401), weight (0.13), BMI (0.182), waist circumference (0.231), hip circumference (0.132), height (0.15), current body size perception (0.181), preferred body size (0.119) and preferred body size of the opposite gender (0.14). For normotensives, a 1 cm increment in waist circumference was associated with an increase in systolic blood pressure by 0.35 mmHg in those younger than 50 years of age. In older participants, an increase in BMI by 1 kg/m 2 led to an increase in systolic blood pressure by 1.1 mmHg. Thirty-two per cent of the participants had hypertension. Less than 10% of the interindividual differences in blood pressure resulted from variations in body dimensions/or body size perception. Significantly, 66.5 versus 51.9% of hypertensive and normotensive individuals, respectively, desired a larger body size for self/spouse. Conclusion: The results indicated a dominant preference for larger body sizes, whereas body dimension predicted blood pressure only to a very limited degree.